New discussion concerning to optimal control for semilinear population dynamics system in Hilbert spaces - Patel, Rohit; Shukla, Anurag; Nieto, Juan J.; Vijayakumar, Velusamy; Jadon, Shimpi Singh (Nonlinear Analysis: Modelling and Control, 2022)
The objective of our paper is to investigate the optimal control of semilinear population dynamics system with diffusion using semigroup theory. The semilinear population dynamical model with the nonlocal birth process is transformed into a standard abstract semilinear control system by identifying the state, control, and the corresponding function spaces. The state and control spaces are assumed to be Hilbert spaces. The semigroup theory is developed from the properties of the population operators and Laplacian operators. Then the optimal control results of the system are obtained using the C0-semigroup approach, fixed point theorem, and some other simple conditions on the nonlinear term as well as on operators involved in the model.